Digitization impact and it's challenges on the music publishing practise. Case study: the Malaysian music industry / Alis Suraya Shaharim. - Shaharim, Alis Suraya (2020)
The purpose of this study is to investigate the digitization impacts and it's challenges on the music publishing practise of the Malaysian music industry. This research analyzes how music publishers adapt to the changes of the music publishing practise due to digitization. Specifically, this study focuses on the factors that changed the roles of music publishers in the digital era, the impacts and challenges brought by the technological innovation in the Malaysian music industry, along with the consequences of the impacts and challenges. This study is being conducted using qualitative method of sources from both primary and secondary data. A-set of questions are prepared to the respondents via e-mail interview and also face-to-face interview. The respondents chosen are music industry practitioners who have experienced working in the digital era of the music industry. In short, this research is important because it will prompty provide ideas and insights regarding the impacts and challenges faced by the present Malaysian music industry in this digital age.